The Effect of Company Size, Solvency and Profitability on Audit Opinions Related to Going Concern in Energy Subsector Manufacturing Companies - Muhammad Maftuh Dzikri (CV. Publikasi Indonesia, 2025)
This study aims to analyze and determine the effect of company size, solvency, and profitability on the issuance of going concern audit opinions. The population of this research includes companies in the energy sub-sector manufacturing sector listed on the Indonesia Stock Exchange (IDX) for the period 2018–2021. Using a purposive sampling method, 50 companies were selected as the sample. Secondary data was collected from the official IDX website and each company's website. Data analysis was conducted using statistical methods to examine the relationship between the variables studied. The findings indicate that company size has a positive and significant influence on going concern audit opinions, suggesting that larger companies are perceived to have stronger business continuity prospects. In contrast, solvency and profitability were found to negatively influence the issuance of going concern audit opinions. High levels of debt and low profitability signal financial instability, thereby increasing the auditors' concerns about the company’s future viability. These results highlight the importance for companies to manage their financial health carefully to avoid receiving adverse audit opinions regarding their going concern status. This research contributes to the literature on audit opinion determinants and provides practical insights for company management, auditors, and stakeholders regarding financial strategy and risk management to sustain business operations.